2009
DOI: 10.1158/1078-0432.ccr-08-1815
|View full text |Cite
|
Sign up to set email alerts
|

Trk Receptor Expression and Inhibition in Neuroblastomas

Abstract: Neuroblastoma, the most common and deadly solid tumor in children, exhibits heterogeneous clinical behavior, from spontaneous regression to relentless progression. Current evidence suggests that the TRK family of neurotrophin receptors plays a critical role in these diverse behaviors. Neuroblastomas expressing TrkA are biologically favorable and prone to spontaneous regression or differentiation, depending on the absence or presence of its ligand (NGF) in the microenvironment. In contrast, TrkB-expressing tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
223
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 270 publications
(237 citation statements)
references
References 72 publications
4
223
0
3
Order By: Relevance
“…Whereas the physiologic role of TRKA is relatively well elucidated (4), its involvement in neoplastic transformation and tumor progression was until very recently limited to identification of rearrangements in papillary thyroid carcinoma (PTC), a tumor type characterized by a relatively good prognosis and reports of activation due to presence of putative autocrine loops in neuroblastoma, prostate, pancreatic, and breast cancer (5)(6)(7)(8)(9)(10). However, chromosomal rearrangements involving the NTRK1 gene, resulting in the expression of different TRKA fusion proteins were recently reported by Vaishnavi and colleagues (11) in NSCLC, along with robust preclinical demonstration of the oncogenic potential of the predicted chimeric proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the physiologic role of TRKA is relatively well elucidated (4), its involvement in neoplastic transformation and tumor progression was until very recently limited to identification of rearrangements in papillary thyroid carcinoma (PTC), a tumor type characterized by a relatively good prognosis and reports of activation due to presence of putative autocrine loops in neuroblastoma, prostate, pancreatic, and breast cancer (5)(6)(7)(8)(9)(10). However, chromosomal rearrangements involving the NTRK1 gene, resulting in the expression of different TRKA fusion proteins were recently reported by Vaishnavi and colleagues (11) in NSCLC, along with robust preclinical demonstration of the oncogenic potential of the predicted chimeric proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that high expression of TrkA in neuroblastoma tissue is associated with improved clinical characteristics in patients and lower MYCN gene amplification, while patients in the advanced stages of neuroblastoma usually exhibit lower expression levels of TrkA and the tumors cannot be treated with NGF to inhibit differentiation (24)(25)(26). The NGF/TrkA signaling pathway is important in promoting neuroblastoma differentiation and natural regression (13,27,28). High expression of TrkA protein in neuroblastoma cells is associated with differentiation and regression (28)(29)(30), while lower TrkA expression is associated with increased invasiveness.…”
Section: A B C Dmentioning
confidence: 99%
“…Ras/MAPK and AKT are activated downstream of these signaling pathways. Ras sequentially activates a series of kinases, including RAF1, mitogen-activated protein kinase kinase, mitogen-activated protein kinase (MAPK) and ribosomal S6 kinase (RSK) (13). MAPK and RSK translocate to the nucleus to initiate the activation of transcription factors that regulate NGF-inducible genes, leading to survival and neuronal differentiation.…”
Section: A B C Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The NTRK family plays a role in the development of the nervous system with the modulation of growth, proliferation, repair, maintenance and apoptosis. 1,2 However, NTRK fusions are also present in solid tumors as oncogenic fusions responsible for growth of cancer cells, proliferation, and survival; the presence of these three oncogenes is associate with poor survival in lung cancers. 3,4 NTRK1 oncogenic fusions have been detected by fluorescent in situ hybridization (FISH) or next generation sequencing in about 3% of NSCLC, while NTRK2 and NTRK3 fusions in about 1% of NSCLC of all types.…”
mentioning
confidence: 99%